Sustainable material pathways: Utilizing biomass-derived bio-oils from agricultural wastes to restore aged asphalt binder properties - Yalcin, Beyza Furtana; Yilmaz, Mehmet; Yalcin, Erkut; Kok, Baha Vural (Pergamon-Elsevier Science Ltd, 2026)
This study explores the valorization of agricultural biomass wastes into high-value bio-based materials by evaluating the performance of pyrolysis-derived bio-oils obtained from straw, pine cone, and olive pomace for the rejuvenation of aged asphalt binders. The effectiveness of these biomass-derived bio-oils was comparatively assessed against two commercial rejuvenators to enhance binder reusability using renewable resources. The optimum rejuvenator dosages were determined through penetration, viscosity, and dynamic shear rheometer (DSR) tests, while the associated physical and chemical modifications were investigated using FTIR, SEM-EDS, and elemental analyses. Penetration and viscosity results indicated that all rejuvenators significantly reduced binder stiffness and improved fluidity. DSR analysis indicated that increasing rejuvenator content reduced G*/ sin delta values, reflecting a decrease in binder stiffness and a softening effect of the rejuvenators, which contributes to restoring the viscoelastic balance of the aged binder. FTIR results demonstrated that biomass-derived bio-oils, particularly those from pine cone and straw, effectively reduced carbonyl (C=O) and sulfoxide (S=O) functional groups, indicating strong chemical rejuvenation. SEM-EDS analyses showed that the heterogeneous and porous morphology of bio-oils promoted improved interaction with the asphalt binder. Based on the combined results of the three experimental approaches, the optimum rejuvenator dosages were identified as 25% for commercial products, 35% for pine cone and olive pomace bio-oils, and 45% for straw bio-oil. Overall, the findings highlight that biomass-derived bio-oils produced via pyrolysis offer a sustainable and performance-effective pathway for converting agricultural residues into value-added materials, supporting circular bioenergy and biomass utilization strategies.
Keywords: Biomass valorization; Agricultural waste; Pyrolysis bio-oil; Rejuvenation